Atherogenic and thrombogenic index, acidic composition of lipid fraction of adipose subcutaneous tissue of female ancient autochthonous genetic type (AAGT) Casertana. Preliminary results - Matassino D.; Amerotti F.; Gigante G.; Inglese F.; Quinto M.; Di Luccia A. (Mediterranean livestock production: uncertainties and opportunities, 2008)
The research was performed on samples of adipose subcutaneous and perirenal tissues of 5 Casertana sows, reared in multiple boxes at the ConSDABI experimental farm and slaughtered at ~160 kg of live weight. Casertana is an ancient autochthonous genetic type (AAGT), present nowadays mainly in Campania (Italy), where there is in progress an extensive programme recovery promoted by ConSDABI. The aim of this study was to characterize the lipid component of adipose tissue evaluated for chemical-nutritional and chemical-extranutritional quality. The results showed that, in all samples examined, the most abundant fatty acids were the C18:1 and C18:2; among the saturated fatty acids, the highest values being observed for C16:0. In the case of adipose subcutaneous sites the UFA/SFA ratio is about 2.30, while the perirenal fat shows a UFA/SFA ratio of about 1.60. These results highlighted that the subcutaneous adipose tissue of Casertana AAGT is a source of fatty acids with functional features to human health and therefore can be conveniently inserted in a correct diet.
2. Seminar of the Scientific-Professional Network on Mediterranean Livestock Farming (RME), 2006/05/18-20, Zaragoza, (Spain)